Adaptation in Mandarin tone production with pitch-shifted auditory feedback: influence of tonal contrast requirements. Issue 6 (3rd July 2018) - Feng, Yongqiang; Xiao, Yan; Yan, Yonghong; Max, Ludo
ABSTRACT: We investigated Mandarin speakers' control of lexical tone production with F0-perturbed auditory feedback. Subjects produced high level (T1), mid rising (T2), low dipping (T3), and high falling (T4) tones in conditions with (a) no perturbation, (b) T1 shifted down, (c) T1 shifted down and T3 shifted up, or (d) T1 shifted down and T3 shifted up but without producing other tones. Speakers and new subjects also completed a tone identification task with unaltered and F0-perturbed productions. With only T1 perturbed down, speakers adapted by raising F0 relative to no-perturbation. With simultaneous T1 down and T3 up perturbations, no T1 adaptation occurred, and T3 adaptation occurred only if T2 was also produced. Identification accuracy with stimuli representing adapted productions was comparable to baseline, but with simulated non-adapted productions it was reduced for T2 and T3. Thus, Mandarin speakers' adaptation to F0 perturbations is linguistically constrained and serves to maintain tone contrast.